Large litter size increases oxidative stress and adversely affects nest-building behavior and litter characteristics in primiparous sows - Lee, Juho; Shin, Hyeonwook; Jo, Janghee; Lee, Geonil; Yun, Jinhyeon (Frontiers in Veterinary Science, 2023)
The study examined 24 primiparous sows (Landrace × Large white) and their offspring, which were grouped based on litter size: NORMAL (n = 8, average litter size 11.5 ± 1.2), with litter size between 7 and 14, and LARGE (n = 16, average litter size 15.9 ± 1.0), with litter size between 15 and 20. Sows were group-housed during gestation, and housed in an adjustable loose housing system (2.4 × 2.3 m) during farrowing and lactation. All the sows were confined in the farrowing crates (0.6 × 2.3 m) for 7 days after the onset of parturition. Saliva samples of sows were collected on days 35, 21, and 7 before farrowing (D-35, D-21 and D7, respectively), and on days 1, 7, and 28 after farrowing (D1, D7, and D28, respectively) to measure the levels of Trolox equivalent antioxidant capacity (TEAC), hydrogen peroxide (H2O2), advanced oxidation protein products (AOPP), and tumor necrosis factor-alpha (TNF-α). Colostrum samples were collected for oxytocin and prolactin assays. Nest-building behavior (NB) for 24 h before parturition and farrowing was observed through video analysis. The results showed that LARGE sows had higher levels of H2O2 on D1 and D7 and AOPP during late gestation (p < 0.05, for all) and lower TEAC levels during late gestation and on D7 and D28 after farrowing (p < 0.05, for all) than NORMAL sows. Additionally, LARGE sows tended to have higher levels of TNF-α on D1 and D7 (p < 0.10, for both). LARGE sows showed shorter duration and lower frequency of NB during 24–12 h before parturition (p < 0.05, for both), and tended to have lower prolactin levels (p = 0.10). Furthermore, large sows tended to show longer farrowing duration and higher stillbirth rate (p = 0.06, p = 0.07, respectively). In conclusion, this study confirmed that large litter size may increase oxidative stress in sows during late gestation and lactation. The data also suggested that this could adversely impact prolactin release, leading to reduced NB.